Cell surface vimentin: a natural human immune response target for immunotherapy - Glassy, Mark C. (Frontiers in Molecular Medicine, 2025)
Natural human monoclonal antibodies obtained from sentinel lymph nodes of cancer patients identify cell surface vimentin. One of these vimentin-reactive antibodies, pritumumab, has been used to treat brain cancer patients. This review summarizes data on mAbs reactive with cell surface vimentin and their origin from lymph nodes of cancer patients.